Pigment production by a newly isolated strain Pycnoporus sanguineus SYBC-L7 in solid-state fermentation - Meng, Di; Shao, Xuan; Luo, Shou-Peng; Tian, Qiao-Peng; Liao, Xiang-Ru (Frontiers in Microbiology, 2022)
Natural pigments are playing important roles in our daily lives. They not only make products colorful but also provide various health benefits for humans. In addition, Pycnoporus genus, listed as food- and cosmetic-grade microorganism, is one of promising organisms for developing natural pigments. In this study, a new fungal strain with high efficiency in producing intense orange pigments was isolated and identified as Pycnoporus sanguineus SYBC-L7. Different agro-industrial wastes were applied to evaluate the growth and pigment production of strain SYBC-L7. SYBC-L7 can grow rapidly and effectively produce pigments using wood chips as substrate in solid-state fermentation (SSF). Culture conditions were also optimized for value-added pigments production and the optimum production conditions were glucose as carbon source, ammonium tartrate as nitrogen source, initial pH 6.0, and relative humidity of 65%. Pigment components, cinnabarinic acid, tramesanguin, and 2-amino-9-formylphenoxazone-1-carbonic acid were confirmed by liquid chromatography mass spectrometry. Meanwhile, an agar plate diffusion assay was performed to evaluate the antimicrobial activity of the pigment. These pigments showed more significant inhibition of Gram-positive than Gram-negative bacteria. The results showed that Pycnoporus sanguineus SYBC-L7 was able to cost-effectively produce intense natural orange pigments with antibacterial activity in SSF, which is the basis of their large-scale production and application.